New Projects in the Process of Public Administration Transformation - Nigmatovna , Rakhimova Dilfuza (Indonesian Journal of Public Administration Review, 2025)
This article examines a range of newly initiated projects aimed at enhancing the effectiveness and quality of public administration. It provides a detailed analysis of the key challenges and systemic shortcomings currently affecting the public administration system, including organizational, institutional, and human resource–related issues. The study also offers an authorial interpretation and conceptual definition of the public administration system, framing it as an integrated mechanism of institutions, processes, and competencies designed to deliver public services and implement state policy. Furthermore, the strengths and existing capacities of the public administration system are evaluated, highlighting areas that provide a foundation for sustainable reform. Based on this analysis, the article proposes practical and strategic recommendations for improving public administration, with particular emphasis on modernization, innovation, and institutional resilience. In addition, the study introduces new perspectives on the development of civil servant competencies, outlining emerging trends in professional skills, leadership, and adaptability required to meet the evolving demands of contemporary governance.